Structural influence of transition metal (Sc, Y, and Lu) atoms inside gold nanoparticles. Issue 12 (21st March 2017) - Zhao, Li Xia; Hijikata, Yuh; Irle, Stephan
Abstract : We theoretically investigated the influences of dopant transition metal atoms on structures and stability of gold nanoparticles. The optimized structures of Au3 M and Au3 M in an Au32 cage (M = Au, Sc, Y, and Lu) obtained using relativistic density functional theory, show different configurations. Substitutions of one Au atom in the Au4 cluster by only one M atom cause the Au3 M clusters to form equilateral triangles where M atoms prefer the central position, which is different from the original rhombus structure of a pure Au4 cluster. All Au3 M nanoparticles, however, assume stable tetrahedral configurations in the Au32 cage. Analysis of electronic structures indicates that the equilateral triangle Au3 M nanoparticles have higher chemical stability, in other words, lower reactivity than Au3 M@Au32, while interaction energies between M and Au atoms in the Au3 M are smaller than those in Au3 M@Au32 . Different amounts of charge transfer and orbital hybridizations between the Au and M cause the change of the chemical stability and interaction energies. Our results indicate the potential manipulation of gold nanoparticle reactivity by metal substitution. Abstract : Substitutions of one Au atom in rhombohedral Au4 clusters by one transition metal M (M= Sc, Y, and Lu) atom induces an Au3 M transformation to equilateral triangles, where the doping atoms occupy the center of the triangles, and Au3 M units tend to take tetrahedral configurations in the Au32 cage. This insight on the structural influence of transition metal in gold nanoparticles could potentially impact the design and the applicability for catalytic reactions of such bimetallic materials.